Gold Rush 2.0: US Defense Political Economy Amid Dollar Decline and Bullion Rise - Simamora, Yohana Meyrida; Perwita, Anak Agung Banyu; Ramsi, Oktaheroe (International Journal of Humanities, Education, and Social Sciences, 2025)
The global financial system is undergoing a profound shift that challenges the reserve currency dominance of the US dollar, driven by escalating national debt, persistent inflation, and intensifying geopolitical tensions. This environment has triggered what can be described as “Gold Rush 2.0,” marked by rising gold prices and declining confidence in fiat currencies. A critical inflection point is evident in the fact that US debt servicing costs ($970 billion in FY2024) have surpassed defense spending ($886 billion), crossing the so-called “Ferguson Limit,” where great powers face heightened risks of decline. This fiscal strain is further compounded by the “Triffin Dilemma,” which requires persistent trade deficits to sustain global dollar liquidity while simultaneously eroding confidence in the currency and deepening debt accumulation. Against this backdrop, the study examines how these dynamics reshape the US defense political economy by constraining budgetary flexibility, hindering modernization, and influencing strategic priorities. Empirical analysis reveals a negative correlation between rising debt servicing obligations and defense budget growth, alongside evidence of central banks increasing gold reserves as a sign of de-dollarization. The study concludes that weakening US economic hegemony carries significant implications for national security and global stability, underscoring the need for strategic recalibration in defense and fiscal policy.